METODE BERCERITA ISLAMI DALAM MENANAMKAN NILAI AKHLAK PADA ANAK USIA DINI - Hasan Yusuf; Iis Paryanti; Olga Nurbaduri; Reina Shira Avissa (LPPM IAD Probolinggo, 2026)
Instilling moral values in early childhood is a very important part of Islamic education because at this stage, children are in the phase of basic character formation. However, the use of less engaging learning methods can hinder children's understanding and appreciation of moral values. This study aimed to examine the effectiveness of Islamic storytelling methods in instilling moral values in early childhood. This study used a qualitative approach in field research. Data were collected from various sources, such as books, scientific journals, and other relevant references, and then analyzed using content analysis techniques. The results of the study show that the Islamic storytelling method is effective in instilling moral values such as honesty, responsibility, patience, and love among children. Islamic stories help children understand moral values through the example of the characters and support children's social, emotional, and language development. In addition, this method increases children's participation in the learning process because it aligns with their developmental characteristics. Thus, the Islamic storytelling method can be an effective strategy for forming Islamic characters in early childhood and needs to be applied consistently in the learning process.